Work‐related musculoskeletal symptoms among otolaryngologists by subspecialty: A national survey. (12th September 2017) - Ho, Thuy‐Van Tina; Hamill, Chelsea S.; Sykes, Kevin J.; Kraft, Shannon M.
Abstract : Objective: Given the high prevalence of work‐related musculoskeletal symptoms, increased appreciation for workplace ergonomics is critical. The purpose of this study is to assess work‐related musculoskeletal symptoms and injury among otolaryngologists across subspecialties, as well as to quantify the understanding and application of ergonomic principles in the operating room. Study Design: Cross‐sectional study. Methods: An online REDCap survey was distributed electronically to University of Kansas faculty, alumni, and residents; members of the American Academy of Facial Plastic and Reconstructive Surgery; and residency program coordinators for distribution to residents and faculty between August 2016 and March 2017. The survey assessed caseload, ergonomic practices, and associated musculoskeletal symptoms by type of procedure and impact of symptoms on surgeon practice. Results: The survey was distributed to 3, 006 individuals. We received 377 responses (12.5%), with 63.9% reporting symptoms. The majority of respondents began to experience symptoms in residency or fellowship. Neck and shoulder were the most affected body areas across all types of surgeries. One‐third of surgeons were formally taught or actively sought information on ergonomics principles. Among those who applied ergonomics in practice, 69.6% observed improvement in their symptoms. Conclusion: Although musculoskeletal issues are prevalent among otolaryngologists, awareness of surgical ergonomics principles among otolaryngologists remains limited. Early instruction in ergonomic principles is important because work‐related musculoskeletal symptoms commonly present in residency. Most respondents reporting the application of ergonomic principles also acknowledge symptom improvement. Level of Evidence: NA. Laryngoscope, 128:632–640, 2018